2016
DOI: 10.1002/ange.201604615
|View full text |Cite
|
Sign up to set email alerts
|

Schwefel in der modernen Materialwissenschaft

Abstract: Schwefel ist eines der häufigsten Elemente im Universum, fällt als Hauptnebenprodukt bei der Erdölraffination an und stellt ein häufiges Reaktionszentrum in biologischen Systemen dar. Die Forschung über Schwefel ist daher breit gefächert und hat große Relevanz und Auswirkungen auf unser tägliches Leben. So hat das Interesse an schwefelbasierten Reaktionen in den letzten zehn Jahren eine deutliche Wiederbelebung erfahren. Weitere relevante Themengebiete sind Forschungen zur Verbesserung von Energieeffizienzen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 203 publications
0
9
0
Order By: Relevance
“…Recently this process was accurately described and nicknamed as “inverse vulcanization” by W. Chung and J. Pyun et al [2] because of its contrary nature to classic sulfur vulcanization of rubber. This has drawn new attention to sulfur-based copolymers for various advanced materials applications [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently this process was accurately described and nicknamed as “inverse vulcanization” by W. Chung and J. Pyun et al [2] because of its contrary nature to classic sulfur vulcanization of rubber. This has drawn new attention to sulfur-based copolymers for various advanced materials applications [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Inverse vulcanization is a process by which sulfur radicals are exposed by the heating of sulfur and reacted with comonomer molecules that have available π electrons to bind, thus forming sulfur-rich polymers . The resulting polymers are stable, can be molded, and have found use in various applications , including as battery cathode materials, ,, dye-sensitized solar cells, , or as infrared-transmitting optical lenses. , Since the discovery of this process, numerous compounds have been utilized as comonomers, including monovinyl, divinyl, trivinyl, dialkynyl, and renewable molecules. , The properties of the resulting polymers can vary significantly based on the comonomer used to bind with the sulfur. ,, It has also been reported that additional π bonds improve the stability of the final polymer . The first inverse vulcanized polymer reported was poly­(S- r -DIB), where “S” represents sulfur, “r” represents the random nature of the comonomer branching within the polymer, and “DIB” represents 1,3-diisopropenyl benzene .…”
mentioning
confidence: 99%
“…I nverse vulcanization is a process by which sulfur radicals are exposed by the heating of sulfur and reacted with comonomer molecules that have available π electrons to bind, thus forming sulfur-rich polymers. 1 The resulting polymers are stable, can be molded, and have found use in various applications 2,3 including as battery cathode materials, 1,4,5 dye-sensitized solar cells, 6,7 or as infrared-transmitting optical lenses. 8,9 Since the discovery of this process, numerous compounds have been utilized as comonomers, including monovinyl, 10 divinyl, 11 trivinyl, 12 dialkynyl, 13 and renewable molecules.…”
mentioning
confidence: 99%
“…It is indeed one of the main side products of crude oil refining, with more than 60 million tons produced annually. 1 Even the relatively low operating voltage of sulfur-based cathodes, at around 2 V vs. Li/Li + , can be considered as a potential advantage, making it intrinsically safer. 2 Furthermore, the high specific gravimetric capacity of sulfur enables the remarkable specific energy of about 2600 W h kg −1 .…”
mentioning
confidence: 99%